Tumor Suppressor miRNA in Cancer Cells and the Tumor Microenvironment: Mechanism of Deregulation and Clinical Implications - Otmani, Khalid; Lewalle, Philippe (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs) are noncoding RNAs that have been identified as important posttranscriptional regulators of gene expression. miRNA production is controlled at multiple levels, including transcriptional and posttranscriptional regulation. Extensive profiling studies have shown that the regulation of mature miRNA expression plays a causal role in cancer development and progression. miRNAs have been identified to act as tumor suppressors (TSs) or as oncogenes based on their modulating effect on the expression of their target genes. Upregulation of oncogenic miRNAs blocks tumor suppressor genes and leads to tumor formation. In contrast, downregulation of miRNAs with TS function increases the translation of oncogenes. Several miRNAs exhibiting TS properties have been studied. In this study, we focus on recent studies on the role of TS miRNAs in cancer cells and the tumor microenvironment. Furthermore, we discuss how TS miRNA impacts the aggressiveness of cancer cells, with focus of the mechanism that regulate its expression. The study of the mechanisms of miRNA regulation in cancer cells and the tumor microenvironment may paved the way to understanding its critical role in the development and progression of cancer and is likely to have important clinical implications in the near future. Finally, the potential roles of miRNAs as specific biomarkers for the diagnosis and prognosis of cancer and the replacement of tumor suppressive miRNAs using miRNA mimics could be promising approaches for cancer therapy.